Nursing, midwifery, and allied health professions research capacities and cultures: a survey of staff within a university and acute healthcare organisation - S. Palmer; J. Coad; J. Gamble; C. Jones; L. Lees-Deutsch; D. McWilliams; E. Murphy; R. Kneafsey (BMC, 2023)
Abstract Background There is an increasing focus on the development of research capacity and culture in Nursing, Midwifery and Allied Health Professions (NMAHP). However, better understanding of the existing research success and skills, motivators, barriers, and development needs of NMAHP professionals is required to inform this development. This study sought to identify such factors within a university and an acute healthcare organisation. Methods An online survey, incorporating the Research Capacity and Culture tool, was administered to NMAHP professionals and students at a university and an acute healthcare organisation in the United Kingdom. Ratings of success/skill levels of teams and individuals were compared between professional groups using Mann-Whitney U tests. Motivators, barriers, and development needs were reported using descriptive statistics. Descriptive thematic analysis was used for open-ended text responses. Results A total of 416 responses were received (N&M n = 223, AHP n = 133, Other n = 60). N&M respondents were more positive than their AHP counterparts about the success/skill levels of their teams. There were no significant differences between N&M and AHP in their ratings of individual successes/skills. Finding and critically reviewing relevant literature were identified as specific individual strengths; with weaknesses in securing research funding, submitting ethics applications, writing for publication, and advising less experienced researchers. The main motivators for research were to develop skills, increased job satisfaction, and career advancement; whilst barriers included lack of time for research and other work roles taking priority. Key support needs identified included mentorship (for teams and individuals) and in-service training. Open-ended questions generated main themes of 'Employment & staffing', 'Professional services support', 'Clinical & academic management', 'Training & development', 'Partnerships' and 'Operating principles'. Two cross-cutting themes described issues common to multiple main themes: 'Adequate working time for research' and 'Participating in research as an individual learning journey'. Conclusions Rich information was generated to inform the development of strategies to enhance research capacity and culture in NMAHP. Much of this can be generic but some nuances may be required to address some specific differences between professional groups, particularly related to perceived team success/skills and priorities identified for support and development.